2021
DOI: 10.1155/2021/9916881
|View full text |Cite
|
Sign up to set email alerts
|

Construction of the circRNA-miRNA-mRNA Regulatory Network of an Abdominal Aortic Aneurysm to Explore Its Potential Pathogenesis

Abstract: Background. Abdominal aortic aneurysm (AAA) is a progressive cardiovascular disease, which is a permanent and localized dilatation of the abdominal aorta with potentially fatal consequence of aortic rupture. Dysregulation of circRNAs is correlated with the development of various pathological events in cardiovascular diseases. However, the function of circRNAs in abdominal aortic aneurysm (AAA) is unknown and remains to be explored. This study is aimed at determining the regulatory mechanisms of circRNAs in AAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Marie et al reported that SELL was associated with the development of AAA ( 59 ). Furthermore, several bioinformatics studies revealed that CCR7 is one of the hub genes of AAA ( 60 , 61 ). Our findings and previous investigations suggest that these genes might be involved in the development of AAA and could be potential biomarkers for AAA, but their diagnostic value needs further validation.…”
Section: Discussionmentioning
confidence: 99%
“…Marie et al reported that SELL was associated with the development of AAA ( 59 ). Furthermore, several bioinformatics studies revealed that CCR7 is one of the hub genes of AAA ( 60 , 61 ). Our findings and previous investigations suggest that these genes might be involved in the development of AAA and could be potential biomarkers for AAA, but their diagnostic value needs further validation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, numerous studies have shown that the ceRNA networks regulation, that is the interaction among circRNAs, miRNAs, and mRNAs, was identified to widely exist in various diseases in different species (64)(65)(66). To investigate the ceRNA network and the functions of circRNAs against APEC infection in chicken macrophages, a putative circRNA-miRNA-mRNA network was constructed in current study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, hsa_circ_0087352 was reported to promote the inflammatory response of macrophages in AAA by adsorbing hsa-miR-149-5p ( Murray and Wynn, 2011 ). Three other circRNAs, hsa_circ_0011449, hsa_circ_0081968 and hsa-let-7f-5p , were found to be correlated with the occurrence of AAA by regulating some other inflammatory cytokines, such as SOD2 and CCR7 ( Zhang et al, 2021 ). Recently, the crosstalk between circRNAs and m6A methylation is gradually being revealed.…”
Section: Discussionmentioning
confidence: 99%